Antagonistic and protective effects against Salmonella enterica serovar typhimurium by Lactobacillus murinus in the digestive tract of gnotobiotic mice - Vasconcelos,Ana Luiza Sampaio (2003)
In the present study, production of antagonistic substances by Lactobacillus murinus against enteropathogenic bacteria was evaluated in vivo as well as a possible protective effect against an oral challenge with Salmonella Typhimurium using a gnotobiotic animal model. A higher mean survival time (P < 0.05) was observed in L. murinus-associated animals (7.89 ± 3.83 days) when compared with the control ones (4.44 ± 0.73 days). Lactobacillus murinus exerted a potent antagonistic effect in vivo against S. sonnei and to a lesser extent against S. Typhimurium as revealed by inhibitory halos around the feces of Lactobacillus-associated animals. Diameters of inhibitory halos around intestinal contents increased along the intestine tract, following proportionally the L. murinus population levels in the respective intestinal portions. Concluding, the present study showed that L. murinus association in gnotobiotic mice delayed the death after an oral challenge with S. Typhimurium and that inhibitory diffusible compounds obtained in in vitro assays were also produced in vivo and may be responsible for this effect.